Peculiarities of Heart Rhythm Regulation at Different Types of Cold Acclimation in Rats - Lutsenko, Dmytro G.; Shylo, Aleksandr V.; Marchenko, Larisa N.; Perskiy, Yevgeniy E.; Babiychuk, Georgiy A. (Problems of Cryobiology and Cryomedicine, 2013)
It has been shown that the initial level of autonomic regulation of heart rate is of great important during cold acclimation. Animals with different initial level of heart rate, SDNN, TP, HF, LF and LF/HF during long-term regimens of cold acclimation implement various strategies of autonomic response which are different in level of sympathetic and parasympathetic involvement in heart rate regulation. At a short-term cold acclimation such splitting of vegetative response does not occur.Probl Cryobiol Cryomed 2013; 23(2):105–115.